153 SYSTEMIC TO PULMONARY COLLATERALS IN A PREMATURE INFANT WITH BRONCHOPULMONARY DYSPLASIA. Issue 1 (1st January 2007) - Evans, W. N.; Acherman, R. J.; Mayman, G. A.; Rothman, A.; Luna, C. F.; Collazos, J. C.; Restrepo, H.
Abstract : Introduction: Systemic to pulmonary artery collaterals (SPCs) occur in a variety of pathologic conditions, including congenital heart disease, chronic pulmonary infections, lung tumors, pulmonary emboli, and bronchopulmonary dysplasia. SPCs may result in symptomatic left-to-right shunts. We describe a preterm infant with two SPCs who we weaned from chronic supplemental oxygen following coil embolization of persistent SPCs. Case: A 580 g female infant product of a twin pregnancy was born by cesarean section at 28 weeks' gestation. The patient was hospitalized for a total of 116 days. On day 13 of life an echocardiogram demonstrated a patent ductus arteriosus and left ventricular volume overload, requiring surgical ligation. After surgery the infant continued to experience pulmonary congestion and ventilator dependency. Extubation was successful at 51 days of age, but the patient continued to receive oxygen via nasal canula. On day 98, the echocardiogram demonstrated SPCs, and a cardiac catheterization was performed. The aortogram showed two small to moderate collaterals from the descending aorta to the right lung, each measuring approximately 1.5 mm in diameter. Both were occluded by coil embolization. Nine days after the procedure, the infant was weaned to room air. Conclusion: SPCs may contribute to prolonged ventilatory support in premature infants. SPCs can be demonstrated by echocardiographic color Doppler interrogation of the aortic arch and the proximal descending aorta. Coil embolization by interventional cardiac catheterization is indicated in symptomatic patients. Careful echocardiographic evaluation is necessary to rule out SPCs in premature infants with a prolonged supplemental oxygen requirement.